Long-term effects of 100% renewable generation on the Colombian power market. (December 2018) - Zapata, Sebastian; Castaneda, Monica; Jimenez, Maritza; Julian Aristizabal, Andres; Franco, Carlos J.; Dyner, Isaac
Abstract: The power industry is changing worldwide from fossil-based energies to renewables, this trend has been mainly fostered by governments seeking to reach decarbonisation. In particular, renewable energies as solar and wind pose benefits and challenges on traditional power system, e.g., they are environmentally friendly but their intermittency and seasonality is a challenge for security of supply. Though, this is not obstacle for countries to produce almost 100% of its electricity from renewables, such is the case in Costa Rica, Paraguay and Iceland. In this context, and given multiple uncertainties tied to the spread of renewable energies, this paper uses a simulation model to analyse a scenario with 100% renewable energy supply. This paper concludes that for the Colombian case, a large hydroelectric component and its complementarity with solar and wind reduce prices and increase energy efficiency, while helping security of supply.